Nodulation, contribution of biological N2 fixation, and productivity of the common bean (Phaseolus vulgaris L.) inoculated with rhizobia isolates. - MOREIRA, L. P. (2017)
The common bean has a great economic, social, and nutritional importance and requires high levels of nitrogen for its cultivation. The plant in symbiosis with rhizobia bacteria can benefit from biological nitrogen fixation (BNF). To assess the agronomic efficacy of rhizobia isolates on the nodulation, contribution of BNF and productivity of the common bean, two experiments were conducted in separate locations. Seventeen Rhizobium tropici isolates were selected and compared with three commercial Rhizobium spp. strains: CIAT 899 and H12 (R. tropici) and PRF 81 (R. freirei). The variables analyzed were: number of nodules (NN), nodules dry weight (NDW), root dry weight (RDW), leaf area (LA), shoot dry weight (SDA), total nitrogen in shoots (Total-N), number of pods (NP), number of grains (NG), grain yield (GY), percentage of nitrogen derived from BNF (Ndfa%), and total nitrogen derived from BNF in the shoots (NdBNF). Inoculation with R. tropici isolates promoted significant gains in nodulation, growth, and productivity of the common bean. About 50% of the isolates promoted GY rates equal to or superior to the nitrogen treatment (NT) and to the standard strains CIAT 899, PRF 81, and H12. Among the best isolates, the Ndfa% ranged from 64.2% to 75.8%, with NdBNF ranging from 802.91 to 1037.56 mg plant-1. The isolate JPrG10A6 of Rhizobium tropici provided high values of NdBNF and GY, showing great potential to be used commercially as inoculant of the common bean crop.